Religious Crisis And The Spiritual Journey In T.s.eliot's " The Wast Land" - Bellour, Leila (Université de M'sila, 2016)
In T.S.Eliot's " The wast land"there is a quest for psychological and spiritual unity;wich is vindicated in the poem's pattern of a spiritual journey.Reading the poem as such provides the reader with a tie that binds its fragments, albeit being said to be formless .As the paperevincs,the ultimate panacea to the shell-shock's problems is believed to hinge on religion.Such a remedy makes possible the unity of the modern man's fragmented self. In an age marked by spiritual sterility and sexual promiscuity, religion is the fructifying power that can restore fertility to the spiritual aridity of modern civilization . Despite his theory of impresionality,the poem is also about Eliot's religious questioning and questing.
Keywords: Wasteland -Eliot -Spiritual-Poem -sterility reading.